(untitled) (Revista horizonte, 2013)
The objective of this research is to identify, through the application of a circuit, the level of motor performance of children in transition II with the presence and absence of a Physical Education Teacher (PEF) at the Monteverde and Alemania kindergartens in the city of Temuco. Methods: The type of research contemplates a quasi-experimental, exploratory-descriptive, cross-sectional, quasi-experimental design, with a mixed approach. The sample was selected under a non-probabilistic criterion, by convenience that included 12 subjects, distributed in 5 females and 6 males, who are in the range of 5 years of age. Results: The results indicate that children with the presence of PEF achieve a higher frequency of compliance (66.7%) in most of the tests compared to subjects who do not have this professional (33.3%). Another striking aspect corresponds to the lowest motor performance, which belongs to a subject from the Kindergarten without PEF, who completed 21 of the 55 items that make up the circuit; while the subject with the best motor performance is part of the Kindergarten with the presence of PEF, who completed 52 items, which suggests a familiarization with this type of work. Conclusion: Finally, differences are observed in the motor performance of children in transition II with the presence and absence of PEF; however, these results are not essentially attributable to the presence of this professional.